European transition at twenty: Assessing progress in countries and sectors - Erik Berglöf; Lise Bruynooghe; Heike Harmgart; Peter Sanfey; Helena Schweiger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This study gauges the status of transition in the formerly centrally planned economies of Eastern Europe and Central Asia, using a broad approach that compares countries with respect to their business environment, competition, and managerial practices; and assesses transition progress at the level of 13 economic sectors. The largest transition gaps remain in Central Asia and some Eastern European and Western Balkans countries. However, significant reform needs also remain in some Central European and Baltic countries, particularly in energy efficiency, transport, and in the financial sector where regulatory regimes require strengthening and local capital markets need to be developed.
Keywords: P20; P23; M1; L4; 330; transition; economic reform; managerial practices; competition; business environment